Hot melt film, battery cell and battery
By using hot melt film material in steel-cased lithium-ion batteries and controlling their compression deformation at specific temperatures to form reliable heat dissipation channels, the safety hazard of thermal runaway in steel-cased lithium-ion batteries at high temperatures is solved, and the safety and sealing performance of the batteries are improved.
Patent Information
- Application Number
- CN202411352900.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
When steel-cased lithium-ion batteries experience thermal runaway at high temperatures, they cannot effectively dissipate heat, leading to cell combustion. Existing pressure relief valves pose a safety hazard due to leakage or water ingress.
By using hot melt film material, and controlling the percentage of compression deformation to be ≤14% at 100℃ and ≥95% at 200℃, a reliable heat dissipation channel is formed by bonding the three-layer hot melt film with the metal material layer.
Effective pressure relief at high temperatures prevents cell combustion, improves battery safety and sealing performance, while maintaining airtightness and drop resistance at room temperature.
Smart Images

Figure CN119264821A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery technology, and in particular relates to a hot-melt film, a battery core and a battery. Background Art
[0002] Compared with soft-pack batteries, steel-shell lithium-ion batteries have higher impact resistance and high safety performance, but the high strength also increases the risk of thermal runaway. The steel-shell battery itself has small deformation. When the battery cell is at high temperature, gas and heat are rapidly generated inside, which cannot be released and easily cause the battery cell to burn. Therefore, a pressure relief valve is added on one side of the steel shell so that the battery cell can dissipate heat through the opening of the pressure relief valve when it reaches a certain temperature, thus avoiding fire. However, this method brings safety hazards to the battery cell. Liquid leakage or water intrusion is prone to occur at the pressure relief valve, causing the battery cell to swell.
[0003] Therefore, providing a battery with good sealing performance, impact resistance and safety performance has become a problem to be solved. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a hot melt film, a battery cell and a battery. The hot melt film provided by the present invention is applied to the battery, so that the battery has good sealing performance, impact resistance and safety performance.
[0005] The present invention provides a hot melt film. A force of 0.1N is applied to the hot melt film in the thickness direction and the temperature is increased at a heating rate of 5°C / min. Under the condition of 100°C, the compression deformation percentage of the hot melt film is ≤14%; under the condition of 200°C, the compression deformation percentage of the hot melt film is ≥95%.
[0006] Preferably, in the XRD spectrum of the hot melt film, there are at least three characteristic peaks at a 2θ angle position between 10° and 20°, including a first diffraction peak at a 2θ angle of 13.5° to 14.5°, a second diffraction peak at a 2θ angle of 16.3° to 17.3°, and a third diffraction peak at a 2θ angle of 17.9° to 18.9°;
[0007] and / or, there is at least one characteristic peak between 20° and 30°;
[0008] Preferably, in the XRD spectrum of the hot-melt film, the total area of characteristic peaks accounts for 20% to 70% of the total peak area in the XRD spectrum.
[0009] Preferably, under nitrogen atmosphere, the temperature is increased from 25°C at a rate of 5°C / min, and a TG thermogravimetric test is performed on the hot melt film. When the temperature reaches 400°C, the weight loss rate of the hot melt film is ≤5%, and when the temperature reaches 600°C, the weight loss rate of the hot melt film is ≥99%.
[0010] Preferably, the hot melt film comprises a polyolefin compound;
[0011] Preferably, the hot melt film comprises one or more of polypropylene, polyethylene, anhydride-modified polypropylene, ethylene-propylene copolymer, butene-ethylene copolymer and metallocene-modified polypropylene.
[0012] Preferably, the hot melt film is a single-layer structure, and the melting point of the hot melt film of the single-layer structure is 90-130°C.
[0013] Preferably, the hot melt film comprises a first film layer, a support layer and a second film layer arranged in sequence;
[0014] The melting point of the first film layer is 90 to 135°C;
[0015] The melting point of the support layer is 120-170°C;
[0016] The melting point of the second film layer is 90-135°C;
[0017] Preferably, the thickness ratio of the first membrane layer, the support layer and the second membrane layer is (0.5-5):1:(0.5-5), and more preferably (1-3):1:(1-3).
[0018] The present invention also provides a battery cell, comprising:
[0019] A shell body, wherein the shell body is provided with a liquid injection hole;
[0020] A pressure relief valve, the pressure relief valve covers the injection hole, the pressure relief valve comprises a first metal material layer, a second metal material layer and a hot melt film arranged between the first metal material layer and the second metal material layer, the hot melt film comprises the hot melt film according to any one of claims 1 to 7.
[0021] Preferably, a force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is gradually increased at a heating rate of 5°C / min. Within 100°C, the compression deformation percentage of the pressure relief valve in the thickness direction is ≤1%, and at 100°C to 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 7% to 23%.
[0022] Preferably, the hot melt film is connected to the first metal material layer, and the surface of the hot melt film connected to the first metal material layer includes C element and O element, and the mass ratio of C element to O element is between 90:10 and 99.9:0.1;
[0023] And / or, the hot melt film is connected to the second metal material layer, and a surface of the hot melt film connected to the second metal material layer includes C element and O element, and the mass ratio of C element to O element is between 90:10 and 99.9:0.1.
[0024] Preferably, the overflow film area of the hot melt film on the surface of the first metal material layer is 0.03 to 3.5 mm 2 , preferably 0.2 to 3 mm 2 ;
[0025] The area of the inner overflow film of the hot melt film on the surface of the second metal material layer is 0.01 to 2.7 mm 2 , preferably 0.3 to 1.3 mm 2 .
[0026] Preferably, a first film layer is disposed on the surface of the first metal material layer and in contact with the hot-melt film; the dyne value of the first film layer is ≥24;
[0027] And / or, a second film layer is provided on the surface of the second metal material layer that contacts the hot-melt film; and the dyne value of the second film layer is ≥24.
[0028] Preferably, the first metal material layer and the second metal material layer include nickel, nickel alloy or copper-plated nickel.
[0029] Preferably, the second metal material layer is connected to the shell of the battery core;
[0030] The second metal material layer is provided with a first pressure relief hole;
[0031] The hot melt film is provided with a second pressure relief hole;
[0032] Preferably, the shell includes a first side wall, the injection hole is arranged on the first side wall, the pressure relief valve covers the injection hole, one side of the second metal sheet of the pressure relief valve is connected to the first side wall, the side of the second metal sheet facing away from the shell is connected to the hot melt film, and the side of the hot melt film layer facing away from the second metal sheet is connected to the first metal sheet.
[0033] The present invention also provides a battery, comprising the above-mentioned battery cell.
[0034] Compared with the prior art, the present invention provides a hot melt film, a force of 0.1N is applied to the hot melt film in the thickness direction, and the temperature is gradually increased at a heating rate of 5°C / min. Under the condition of 100°C, the compression deformation percentage of the hot melt film is ≤14%; under the condition of 200°C, the compression deformation percentage of the hot melt film is ≥97%. The present invention controls the compression deformation percentage of the hot melt film under the condition of 100°C to avoid the hot melt film from being melted at low temperature of the battery cell, resulting in reduced adhesion at the pressure relief valve, easy leakage, and opening; therefore, the present invention limits the compression ratio at 100°C to within 14%, and the hot melt film can be continuously compressed when the temperature is increased subsequently, until 200°C, the compression deformation percentage of the hot melt film is ≥97%, the pressure relief valve is melted at high temperature, a heat dissipation channel is provided, and the safety performance of the battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the compression deformation percentage test of the hot melt film;
[0036] Figure 2 A schematic diagram of the structure of the hot melt film provided by the present invention; 1 is a first film layer, 2 is a support layer, and 3 is a second film layer;
[0037] Figure 3 It is a schematic diagram of the compression set percentage test of the pressure relief valve;
[0038] Figure 4 A schematic diagram of the local structure of the pressure relief valve provided by the present invention in a battery cell;
[0039] Figure 5 The schematic diagram of the structure of the pressure relief valve from the outside to the inside of the battery is a top view;
[0040] Figure 6 This is a schematic diagram of the structure of the pressure relief valve viewed from the inside to the outside of the battery;
[0041] Figure 7 A schematic diagram of the structure of a battery provided by the present invention;
[0042] Figure 8 This is the XRD spectrum of the hot-melt film provided in Example 1. DETAILED DESCRIPTION
[0043] The present invention provides a hot melt film, a force of 0.1N is applied to the hot melt film in the thickness direction, and the temperature is gradually increased at a heating rate of 5°C / min. Under the condition of 100°C, the compression deformation percentage of the hot melt film is ≤14%; under the condition of 200°C, the compression deformation percentage of the hot melt film is ≥95%.
[0044] In the present invention, a force of 0.1N is used to compress the hot melt film, and the compression deformation of the hot melt film under different temperature conditions is controlled, so that the hot melt film can be opened at a specific temperature and the pressure can be released in time to avoid safety accidents such as fire and explosion caused by inflation of the battery cell.
[0045] The hot melt film thermal compression test (TMA test) method is as follows Figure 1 , Figure 1 Schematic diagram of the compression deformation percentage test of the hot melt film, wherein 1 is a push rod, 2 is a hot melt film, and 3 is a base.
[0046] The test mechanism is set in the heating chamber. When testing, the hot melt film is placed on the surface of the base and in contact with the base. A vertical force of 0.1N is applied to the hot melt film through a push rod. As the temperature in the heating chamber continues to rise, the heat is transferred to the hot melt film, and the hot melt film begins to melt. Under the action of the force, it overflows to the surroundings, and the thickness of the hot melt film decreases.
[0047] Specifically, a force of 0.1 N was applied to the hot melt film in the thickness direction, and the temperature was increased from room temperature at a heating rate of 5° C. / min to test the compression deformation percentage of the hot melt film in the thickness direction under different temperature conditions.
[0048] The calculation formula of the deformation thickness percentage of the hot melt film is shown in Formula I:
[0049] Compression deformation percentage of hot melt film = compression thickness in the thickness direction of hot melt film / initial thickness of hot melt film (Formula I);
[0050] The compressed thickness of the hot melt film in the thickness direction is the difference between the initial thickness of the hot melt film and the thickness of the hot melt film after thermal compression. The initial thickness of the hot melt film is the thickness of the hot melt film at room temperature without compression.
[0051] The present invention controls the compression deformation percentage of the hot melt film at 100°C to avoid the hot melt film from melting at low temperature of the battery cell, which leads to reduced adhesion at the pressure relief valve, easy leakage and opening; therefore, the present invention limits the compression ratio at 100°C to less than 14%, preferably 0.5% to 14%, and can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or any value between 0.5% and 14%.
[0052] The subsequent heating hot melt film can be continuously compressed until 200°C, and the compression deformation percentage of the hot melt film is ≥95%, preferably 97% to 100%, and can be 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, 100%, or any value between 97% and 100%. The hot melt film in the pressure relief valve melts at high temperature, which can provide a heat dissipation channel and improve the safety performance of the battery.
[0053] In the XRD spectrum of the hot melt film, there are at least three characteristic peaks at a 2θ angle position between 10° and 20°, including a first diffraction peak at a 2θ angle of 13.5° to 14.5°, a second diffraction peak at a 2θ angle of 16.3° to 17.3°, and a third diffraction peak at a 2θ angle of 17.9° to 18.9°; there is at least one characteristic peak at a 2θ angle of 20° to 30°;
[0054] In the XRD spectrum of the hot-melt film, the total area of the characteristic peaks accounts for 20% to 70% of the total peak area in the spectrum, and can be 20%, 22%, 25%, 27%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 44%, 45%, 46%, 48%, 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, 70%, or any value between 20% and 70%.
[0055] When the total area of the XRD characteristic peaks accounts for 20% to 70% of the total peak area in the spectrum, the electrolyte resistance of the material can be improved to avoid swelling in the electrolyte environment of the battery cell for a long time, which may lead to failure of the pressure relief valve and cause swelling and leakage of the battery cell.
[0056] In the present invention, under nitrogen atmosphere, the temperature is raised from 25°C at a rate of 5°C / min, and a TG thermogravimetric test is performed on the hot melt film. When the temperature reaches 400°C, the weight loss rate of the hot melt film is ≤5%, preferably 0.5% to 5%, and can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value between 0.5% and 5%; when the temperature reaches 600°C, the weight loss rate of the hot melt film is ≥99%, preferably 99.2% to 100%, and can be 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 100%, or any value between 99.2% and 100%.
[0057] By controlling the thermal weight loss rate of the hot-melt film under different temperature conditions, the fit between the hot-melt film and the steel-shell battery metal can be improved, which is beneficial to the sealing of the battery and prevents leakage. At the same time, it can also be hot-melted at high temperatures to provide a heat dissipation channel and improve the safety performance of the battery.
[0058] In the present invention, the hot melt film comprises a polypropylene compound. Further preferably, the hot melt film comprises one or more of anhydride-modified polypropylene, ethylene-propylene copolymer, butene-ethylene copolymer and metallocene-modified polypropylene.
[0059] In some specific embodiments of the present invention, the hot melt film is a thermoplastic polymer film, the hot melt film is a single-layer structure, and the hot melt film includes one or more of polypropylene, anhydride-modified polypropylene, polyethylene, ethylene-propylene copolymer and butene-ethylene copolymer;
[0060] The melting point of the single-layer hot-melt film is 90-130°C, and can be 90, 95, 100, 105, 110, 115, 120, 125, 130, or any value between 90 and 130°C;
[0061] In some specific embodiments of the present invention, the hot melt film is a thermoplastic polymer film. The hot melt film comprises a first film layer, a support layer and a second film layer arranged in sequence. The first film layer is connected to the second metal material layer, and the second film layer is connected to the first metal material layer. Figure 2 , Figure 2 This is a schematic structural diagram of the hot-melt film provided by the present invention. Figure 2 In the figure, 1 is the first membrane layer, 2 is the support layer, and 3 is the second membrane layer.
[0062] The melting point of the support layer is 120-170°C, and can be 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, or any value between 120 and 170°C;
[0063] The melting point of the first film layer is 90-135°C, and can be 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, or any value between 90 and 135°C;
[0064] The melting point of the second film layer is 90-135°C, and can be 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, or any value between 90 and 135°C;
[0065] Preferably, the hot melt film has a symmetrical structure, and the thickness ratio of the first film layer, the support layer and the second film layer is (0.5-5):1:(0.5-5), which can be 0.5:1:0.5, 1:1:1, 1.5:1:1.5, 2:1:2, 2.5:1:2.5, 3:1:3, 4:1:4, 5:1:5, or any value between (0.5-5):1:(0.5-5), preferably any value between (1-3):1:(1-3).
[0066] In the present invention, preferably, the thickness of the hot-melt film support layer is less than or equal to the thickness of the first film layer or the second film layer.
[0067] In the present invention, the pressure relief valve with a three-layer hot melt film structure can be hot-melted at high temperature to provide a heat dissipation channel; compared with a single-layer hot melt film, a three-layer hot melt film is easier to control the hot pressing thickness. In comparison, the three-layer hot melt film has better electrolyte resistance, so the drop effect is slightly better than the single-layer hot melt film, and the opening effect is slightly worse. Both need to be balanced to achieve excellent performance.
[0068] The present invention also provides a battery cell, comprising:
[0069] A shell body, wherein the shell body is provided with a liquid injection hole;
[0070] A pressure relief valve covers the injection hole, the pressure relief valve includes a first metal material layer, a second metal material layer and a hot melt film arranged between the first metal material layer and the second metal material layer, and the hot melt film includes the hot melt film described above.
[0071] In the present invention, a force of 0.1N is applied to the thickness direction of the pressure relief valve, and the temperature is gradually increased at a heating rate of 5°C / min. Within 100°C, the compression deformation percentage of the pressure relief valve in the thickness direction is ≤1%, and at 100°C to 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 7% to 23%.
[0072] In the present invention, a thermal compression test (TMA test) is performed on the pressure relief valve, and the percentage of the deformation thickness of the pressure relief valve needs to be controlled at different temperature stages.
[0073] The specific test method is: apply a force of 0.1N to the thickness direction of the pressure relief valve, increase the temperature from room temperature at a heating rate of 5℃ / min, and test the compression deformation percentage of the thickness direction of the pressure relief valve under different temperature conditions.
[0074] See also Figure 3 , Figure 3 Schematic diagram of the compression set percentage test of the pressure relief valve, where 1 is the push rod, 2 is the pressure relief valve, and 3 is the base.
[0075] The test mechanism is set in the heating chamber. When testing, the pressure relief valve is placed on the surface of the base, wherein the second metal sheet is placed at the bottom layer and in contact with the base, and the first metal sheet is at the top layer and away from the base. A vertical force of 0.1N is applied to the pressure relief valve through the push rod, and the direction of the force is from the first metal sheet to the vertical direction of the second metal sheet. As the temperature in the heating chamber continues to rise, the temperature is transferred to the hot melt film, the hot melt film begins to melt, and overflows to the surroundings under the action of the force, and the thickness of the pressure relief valve is reduced.
[0076] Specifically, the calculation formula for the compression deformation percentage in the thickness direction of the pressure relief valve is shown in Formula II:
[0077] The compression deformation percentage of the pressure relief valve in the thickness direction = the compression thickness of the pressure relief valve in the thickness direction / the initial thickness of the pressure relief valve Formula II.
[0078] The compressed thickness of the pressure relief valve in the thickness direction is the difference between the initial thickness of the pressure relief valve and the thickness of the pressure relief valve after thermal compression. The initial thickness of the pressure relief valve is the thickness of the pressure relief valve when it is not compressed at room temperature.
[0079] Within 100°C, the compression deformation percentage of the pressure relief valve in the thickness direction is ≤1%; at 100°C to 200°C, when the compression deformation percentage of the pressure relief valve in the thickness direction is 7% to 23%, the pressure relief valve has good sealing, impact resistance and safety performance.
[0080] Specifically, the compression deformation percentage of the pressure relief valve in the thickness direction within 100°C is ≤1%, more preferably 0.1% to 0.8%, and can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, or any value between 0.1% and 0.8%. Controlling the compression deformation percentage of the pressure relief valve in the thickness direction within 100°C to ≤1% can ensure the airtight performance of the battery cell at room temperature, while improving the adhesion between the hot melt film and the first metal material layer and the second metal material layer at room temperature, improving the anti-drop ability of the battery cell, and avoiding leakage of the battery cell between the first metal material layer and the second metal material layer.
[0081] Since both the first metal material layer and the second metal material layer include metal elements, the deformation within 200°C is derived from the hot melt film. The compression deformation percentage of the pressure relief valve in the thickness direction at 100°C to 200°C is 7% to 23%, which can be 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, or any value between 7% and 23%. Preferably, the compression deformation percentage of the pressure relief valve in the thickness direction at 100°C to 200°C is 13% to 22%.
[0082] During the heating and compression process of the hot-pressing valve, the hot-melt film is gradually melted and extruded, and a gap appears between the first metal material layer and the second metal material layer, which can provide a heat dissipation and pressure relief channel to promptly remove the gas and heat generated by the battery, thereby improving the safety performance of the battery. The pressure relief valve is basically non-deformed within 100°C, which can ensure the airtightness of the battery cell at room temperature, while improving the adhesion between the first metal material layer and the second metal material layer at room temperature, improving the drop resistance of the battery cell, and avoiding leakage of the battery cell between the first metal material layer and the second metal material layer, thereby ensuring the impact resistance and sealing performance of the battery.
[0083] The lower the thermal compression deformation temperature of the pressure relief valve, the easier it is for the hot melt adhesive to melt, and the better the hot box safety performance of the battery cell. However, if the thermal deformation temperature is too low, the battery cell will swell during high-temperature charging and discharging, and the battery cell will have poor impact resistance. The present invention can improve the sealing performance of the battery cell and improve the impact resistance by moderately increasing the thermal deformation temperature and improving the adhesion at room temperature.
[0084] In the present invention, the hot melt film is bonded to the first metal material layer, and the surface of the hot melt film and the side connected to the first metal material layer includes C element and O element, and the mass ratio of C element to O element is between 90:10 and 99.9:0.1, and can be 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, 99:1, 99.5:0.5, 99.9:0.1, or any value between 90:10 and 99.9:0.1;
[0085] The hot melt film is bonded to the second metal material layer, and a surface of the hot melt film connected to the second metal material layer includes C element and O element, and the mass ratio of C element to O element is between 90:10 and 99.9:0.1, and can be 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, 99:1, 99.5:0.5, 99.9:0.1, or any value between 90:10 and 99.9:0.1.
[0086] The hot melt film is bonded to the first metal material layer and the second metal material layer. The first metal material layer and the second metal material layer are made of metal and have poor adhesion to the hot melt film. The hot melt film is modified with anhydride to increase the proportion of O in the hot melt film. When the ratio of C and O elements is between 90:10 and 99.9:0.1, high bonding strength between the hot melt film and the first metal material layer and the second metal material layer can be guaranteed.
[0087] In some preferred embodiments of the present invention, a first film layer is provided on the surface of the first metal material layer and in contact with the hot-melt film; the dyne value of the first film layer is ≥24, preferably 24-44, or 22, 24, 25, 26, 28, 30, 32, 34, 35, 36, 38, 40, 42, 44, or any value between 24 and 44.
[0088] A second film layer is provided on the surface of the second metal material layer and in contact with the hot-melt film; the dyne value of the second film layer is ≥24, preferably 24-44, or 22, 24, 25, 26, 28, 30, 32, 34, 35, 36, 38, 40, 42, 44, or any value between 24 and 44.
[0089] By controlling the dyne values on the surfaces of the first film layer and the second film layer, the bonding with the hot melt film can be strengthened and the sealing performance of the pressure relief valve can be improved.
[0090] In the present invention, there is no particular limitation on the preparation method of the first film layer, and any preparation method known to those skilled in the art may be used. The preparation method of the first film layer preferably comprises the following steps:
[0091] After cleaning, degreasing and removing foreign matter from the first metal material layer, the first metal material layer is passivated with a chromium salt or a silane coupling agent to obtain a first film layer;
[0092] The present invention has no particular limitation on the preparation method of the second film layer, and any preparation method known to those skilled in the art may be used. The preparation method of the second film layer preferably comprises the following steps:
[0093] After cleaning, degreasing and removing foreign matters from the second metal material layer, the second metal material layer is passivated with a chromium salt or a silane coupling agent to obtain a second film layer.
[0094] Among them, the chromium salts used to prepare the first film layer and the second film layer independently include one or more of chromium nitrate, chromic anhydride, chromium sulfate, and chromium chlorate, and the silane coupling agent independently includes one or more of bis-[γ-(triethoxysilyl)propyl]tetrasulfide (BTSPS), γ-glycidyl ether propyl trimethoxysilane, bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and 1,2-bis(triethoxysilyl)ethane (BTESE).
[0095] The first metal material layer and the second metal material layer are both passivated, and the first film layer and the second film layer are formed on the surface, respectively, so as to form more contact area with the hot melt film, establish more hydrogen bonds, and improve the bonding ability. Among them, the dyne value can characterize the surface tension of the material. The larger the surface tension, the higher the dyne value, and the better the adhesion of the material. This method can be used to increase the bonding force between the first metal material layer, the second metal material layer and the hot melt film.
[0096] In the present invention, the pressure relief valve covers the position of the injection hole on the shell of the battery cell;
[0097] The second metal material layer is welded to the outer shell of the battery cell;
[0098] The second metal material layer is provided with a first pressure relief hole;
[0099] The hot melt film is provided with a second pressure relief hole;
[0100] The first pressure relief hole, the second pressure relief hole and the liquid injection hole are interconnected.
[0101] See also Figure 4 , Figure 4 A schematic diagram of the local structure of the pressure relief valve provided by the present invention in a battery cell.
[0102] In the present invention, the hot melt film partially overflows the outer surface of the first metal material layer or the second metal material layer, wherein the second metal material layer is in direct contact with the battery cell shell, and there is no direct contact between the first metal material layer and the second metal material layer.
[0103] The hot melt film is cast on both sides between the first metal material layer and the second metal material layer, wherein the hot melt film overflows inward from the surface of the first metal material layer, and the area exceeding the edge of the first pressure relief hole of the second metal material layer is the inner overflow film area, and the inner overflow film area is 0.01-2.7mm 2 , can be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.3, 2.5, 2.7, or 0.01-2.7 mm. 2 Any value between 0.2 and 2 mm is preferred. 2 Any value between 0.2 and 1 mm is more preferred. 2 Any value between
[0104] The hot melt film overflows outward on the surface of the second metal material layer, and the area exceeding the edge of the first metal material layer is the overflow film area, and the overflow film area is 0.03-3.5mm 2 , can be 0.03, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, or 0.03-3.5 mm. 2 Any value between 0.2 and 3 mm is preferred 2 ; More preferably 0.15 to 1.3 mm 2 .
[0105] See also Figure 5 and Figure 6 , Figure 5 In the direction of looking down from the outside to the inside of the battery ( Figure 5 The right figure of the figure is marked with the viewing direction), a schematic diagram of the top view of the pressure relief valve; Figure 6 To follow the battery from the inside to the outside ( Figure 6 The right figure shows the viewing direction, which is a top view of the pressure relief valve.
[0106] When the pressure relief valve is manufactured, the hot melt film is bonded to the surfaces of the first metal material layer and the second metal material layer by hot pressing. During hot pressing, the hot melt film is melted by the heat and overflows to the surrounding areas. The present invention can ensure the bonding force between the first metal material layer, the hot melt film and the second metal material layer by controlling the overflow area.
[0107] If the overflow film area is too small, the adhesion between the first metal material layer, the hot melt film, and the second metal material layer will be weakened; if the overflow film area is too large, the hot melt film extrusion between the first metal material layer and the second metal material layer will increase, which will cause the channel area to decrease during the high-temperature hot melting of the pressure relief valve, and the high-temperature hot box performance will decrease. Therefore, the present invention ensures the sealing performance of the pressure relief valve while ensuring the safety of the battery by controlling the appropriate areas of the overflow glue and the overflow glue.
[0108] By increasing the surface tension of the first metal material layer and the second metal material layer, more coordination bonds and hydrogen bonds can be formed after hot pressing with the acid-modified polypropylene hot melt film, thereby improving the bonding strength; at the same time, the hot melt film's overflow area is regulated by hot pressing, so that the hot melt film is not compressed too thin, resulting in the hot melt adhesive being unable to melt or the opening area being insufficient, and the hot melt adhesive is not compressed too thickly, resulting in insufficient bonding strength at room temperature. In this way, the hot box test of the battery cell is improved while the sealing performance and room temperature impact resistance of the battery cell are improved;
[0109] The present invention has no special limitation on the specific shape of the pressure relief valve. To facilitate processing, in some specific embodiments of the present invention, the first pressure relief hole and the second pressure relief hole are circular, elliptical, square, or rectangular, preferably circular.
[0110] In the present invention, the area of the first pressure relief hole is smaller than or equal to the area of the injection hole on the shell of the battery cell; the area of the second pressure relief hole is smaller than or equal to the area of the first pressure relief hole, and the first pressure relief hole covers the second pressure relief hole in the vertical projection direction.
[0111] The area of the first metal material layer is larger than the total area of the hot melt film and the second pressure relief hole, and the area of the first metal material layer is larger than the area of the second pressure relief hole, and the first metal material layer covers the second pressure relief hole.
[0112] In the present invention, the area of the first metal material layer is greater than the area of the first pressure relief hole on the second metal material layer.
[0113] Furthermore, the hot melt film is a hot melt film ring sheet with an inner diameter of 0.2 to 0.8 mm, which can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or any value between 0.2 and 0.8 mm, and an outer diameter of 1.8 to 2.6 mm, and the outer diameter can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, or any value between 1.8 and 2.6 mm.
[0114] Furthermore, the second metal material layer is a metal ring sheet with an inner diameter of 0.7 to 1.8 mm, which can be 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, or any value between 0.7 and 1.8 mm, and an outer diameter of 3.1 to 3.9 mm, and the outer diameter can be 3.1, 3.2, 3.3, .34, 3.5, 3.6, 3.7, 3.8, 3.9, or any value between 3.1 and 3.9 mm.
[0115] Furthermore, the first metal material layer is a non-porous metal disc with a diameter of 2 to 2.8 mm, which can be 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, or any value between 2 and 2.8 mm.
[0116] Furthermore, the centers of the first metal material layer, the hot-melt film and the second metal material layer are located on the same axis.
[0117] In the present invention, the first metal material layer and the second metal material layer include nickel, nickel alloy or copper-plated nickel. Among them, copper-plated nickel has better thermal conductivity, which helps to increase the temperature of the hot melt film at the pressure relief valve, reach the melting point of the hot melt film, and release heat and pressure in advance.
[0118] A pressure relief valve is welded at the position of the liquid injection hole of the shell, that is, the second metal material layer of the pressure relief valve is in direct contact with the shell and connected by welding. Under high temperature conditions, the battery cell reacts violently to produce gas and heat, and the hot melt adhesive reaches the melting temperature and opens from here to form a heat dissipation and pressure relief channel, thereby improving the hot box performance of the battery cell.
[0119] The present invention further provides a battery, comprising a shell and a pressure relief valve, wherein the shell comprises an outer shell and a liquid injection hole arranged on the outer shell, and the pressure relief valve covers the liquid injection hole.
[0120] See also Figure 7 , Figure 7 This is a schematic diagram of the structure of the battery cell provided by the present invention. Figure 7 In the figure, 1-shell; 2-pressure relief mechanism; 3-pressure relief through hole; 4-electrode positive electrode assembly; 5-electrode negative electrode assembly.
[0121] The battery cell provided by the present invention includes a shell. Preferably, the shell is a steel shell. The outer shell of the shell is composed of a plurality of outer walls. The outer walls are square, rectangular, L-shaped or other special-shaped structures.
[0122] The battery cell provided by the present invention further comprises a liquid injection hole arranged on the side wall of the shell, and the liquid injection hole is used to inject electrolyte into the shell during the manufacturing process of the battery cell.
[0123] The battery cell provided by the present invention further comprises an electrode assembly. The liquid injection hole of the battery cell provided by the present invention, the electrode post hole of the positive electrode post and the negative electrode assembly are located on the same side outer wall of the shell.
[0124] The present invention also provides a lithium ion secondary battery, comprising the above battery core.
[0125] In the present invention, since the first metal material layer and the second metal material layer are made of metal, the deformation within 200°C comes from the hot-melt film, which is mainly caused by the thickness of the deformation of the compressed hot-melt film. During the heating and compression process of the hot-pressing valve, the hot-melt film is gradually melted and extruded, and a gap appears between the first metal material layer and the second metal material layer, which can provide a heat dissipation and pressure relief channel to timely remove the gas and heat generated by the battery, thereby improving the safety performance of the battery; and the pressure relief valve is basically not deformed within 100°C, which can ensure the airtightness of the battery cell at room temperature, while improving the bonding strength of the first metal material layer and the second metal material layer at room temperature, improving the anti-drop ability of the battery cell, avoiding leakage of the battery cell between the first metal material layer and the second metal material layer, and ensuring the impact resistance and sealing performance of the battery.
[0126] Furthermore, the present invention can further improve the adhesion with the hot-melt film by increasing the surface dyne value of the first metal material layer and the second metal material layer at the pressure relief valve and adjusting the overflow of the hot-melt film; at the same time, controlling the compression ratio of the pressure relief valve and the hot-melt film can further improve the adhesion of the battery cell at room temperature and improve the impact resistance.
[0127] In order to further understand the present invention, the hot-melt film, battery cell and battery provided by the present invention are described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0128] The following examples and comparative examples are related to the test methods:
[0129] 1. Thermal compression test:
[0130] (1) Pressure relief valve thermal compression test method
[0131] The test sample is heated at a heating rate of 5°C / min under a set nitrogen atmosphere, and a force of 0.1N is applied to the thickness direction of the pressure relief valve. The pressure relief valve deforms as the temperature rises. The temperature-deformation curve of the test sample can be used to calculate the compression deformation percentage of the pressure relief valve in the thickness direction under different temperature conditions.
[0132] (2) Hot melt film thermal compression test method
[0133] The test sample is heated at a heating rate of 5°C / min under a set nitrogen atmosphere, and a force of 0.1N is applied to the thickness direction of the hot melt film. As the temperature rises, deformation occurs. The temperature-deformation curve of the test sample can be used to calculate the compression deformation percentage of the hot melt film in the thickness direction under different temperature conditions.
[0134] 2. Dyne value test:
[0135] Use the German arcotest dyne pen to draw a 2mm horizontal line on the surface of the pressure relief valve and observe visually. There is no obvious shrinkage within 5 seconds.
[0136] 3. Test methods for battery performance parameters:
[0137] 1. Hot box test:
[0138] 130 degree hot box test: Under 25℃±3℃ environment, discharge at 0.2C to cut-off voltage 3.0V, and let stand for 10min; charge at 0.5C constant current and constant voltage to upper limit voltage 4.5V, cut-off current 0.02C, test voltage, internal resistance and thickness at 25℃±3℃ in full charge state, put the fully charged battery into the test box, and heat up the test box at a temperature rise rate of (5±2)℃ / min. When the temperature in the box reaches 130℃±2℃, keep the temperature constant for 60min; after the test is completed, observe whether the battery cell catches fire. If it catches fire, it fails, otherwise it passes, and record the qualified ratio.
[0139] The higher the pass rate of the hot box test, the better the battery safety performance.
[0140] 2. Impact resistance test:
[0141] At 25℃±3℃, discharge to the lower limit voltage at 0.2C, let stand for 10 minutes, put the battery in a 25℃ constant temperature box, fully charge at 0.7C constant current, cut-off current 0.02C, and drop within 12-24h after full charge; drop the side wall of the pressure relief valve 15 times at a height of 1.5m above the horizontal plane, observe whether the battery leaks, and record the qualified ratio;
[0142] 3. Sealing performance test:
[0143] At 25℃±3℃, discharge at 0.2C to the lower limit voltage, let it stand for 10 minutes, put the battery cell in a 25℃ constant temperature box, fully charge it at 0.7C constant current, and the cut-off current is 0.02C. After fully charged, store the battery cell in a 60℃&95%RH environment, test the battery cell thickness every 3D, record the expansion rate of the 45D battery cell, and it is qualified if the expansion does not exceed 8%, and record the qualified proportion of the battery cell.
[0144] Example 1
[0145] 1) Tablet preparation: The positive electrode active material, the conductive agent carbon black, the binder polyvinylidene fluoride and the solvent are stirred and evenly mixed and then coated on the surface of the positive electrode substrate; wherein the positive electrode substrate is selected from 8μm aluminum foil, and the positive electrode active material is mainly lithium cobalt oxide. After the mixed material is coated, dried and rolled, a positive electrode sheet is obtained; the negative electrode active material, the conductive agent carbon black, the binder SBR styrene butadiene rubber latex and the dispersant CMC and the solvent are stirred and evenly mixed and then coated on the surface of the negative electrode substrate; wherein the negative electrode substrate is selected from 10μm copper foil, and the negative electrode active material is mainly graphite, and then the mixed material is evenly coated, dried and rolled to obtain a negative electrode sheet.
[0146] 2) Winding and welding: Wind the prepared positive electrode sheet, negative electrode sheet and separator simultaneously, weld the positive electrode sheet conductor at the empty foil of the positive electrode sheet, weld the negative electrode sheet conductor at the empty foil area of the negative electrode sheet, stick protective glue on the front and back sides of the conductor welding position, place the separator between the positive and negative electrode sheets, where the separator area > the negative electrode sheet area > the positive electrode sheet area; and obtain the winding core.
[0147] 3) placing the prepared coil core in a steel shell, and obtaining a lithium-ion battery through welding, edge cutting, liquid injection, aging, formation, secondary sealing, and OCV, and then welding a pressure relief valve at the liquid injection position;
[0148] The pressure relief valve is made as follows:
[0149] The first metal material layer and the second metal material layer are treated by acid washing, alkali washing, degreasing, water washing, chromic anhydride passivation, water washing, sealing, water washing and drying to obtain the treated nickel sheet. The dyne value of the nickel sheet and the nickel ring is adjusted by adjusting the concentration of chromium salt and the treatment time.
[0150] The first metal material layer: made of nickel, with a diameter of 2.5 mm, a thickness of 0.15 mm, and a dyne value of 28;
[0151] The second metal material layer: made of nickel, with an inner diameter of 1.1 mm, an outer diameter of 3.4 mm, a thickness of 0.08 mm, and a dyne value of 28;
[0152] The hot melt film adopts a three-layer structure, including a first film layer, a support layer and a second film layer which are compounded in sequence: the thickness ratio of the first film layer, the support layer and the second film layer is 2:1:2, the inner diameter of the hot melt film is 0.6mm, and the outer diameter is 2.3mm;
[0153] The thickness of the first film layer is 32 μm, and the melting point temperature is 103.2°C and 124.5°C;
[0154] The thickness of the support layer is 16 μm and the melting point is 164.5°C;
[0155] The thickness of the second film layer is 32 μm, and the melting point temperature is 103.2°C and 124.5°C;
[0156] After hot pressing the nickel ring and the hot-melt film after the above treatment, the nickel sheet is covered in the center on the other side of the hot-melt film surface, and the three are placed in the center; after the hot pressing is completed, they are welded to the injection hole position of the battery shell;
[0157] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.81mm 2 ;
[0158] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.65mm 2 ;
[0159] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 4.40%; at 200°C, the compression deformation percentage of the hot melt film was 99.35%.
[0160] The hot melt film was tested by XRD, and the results are shown in Figure 8 , Figure 8 This is the XRD spectrum of the hot melt film in the lithium ion battery provided in Example 1. The characteristic peaks of the material include 14.0°, 16.8°, 18.3°, 21.2°, and 23.5°; the total area of the characteristic peaks accounts for 64.3% of the total peak area in the XRD spectrum.
[0161] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.59%.
[0162] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.03%. At 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.94%.
[0163] Example 2
[0164] According to the method of Example 1, the materials of the first metal material layer and the second metal material layer are changed to copper plated with nickel.
[0165] Example 3
[0166] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C;
[0167] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.82mm 2 ;
[0168] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.66mm 2 ;
[0169] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 6.15%; at 200°C, the compression deformation percentage of the hot melt film was 99.19%.
[0170] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 59.0% of the total peak area in the XRD spectrum.
[0171] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.78%.
[0172] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.02%. At 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.83%.
[0173] Example 4
[0174] According to the method of Example 1, the diameter of the first metal material layer is changed to 2.4 mm;
[0175] The melting points of the first and second film layers are 92.3°C;
[0176] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.83mm 2 ;
[0177] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.66mm 2 ;
[0178] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction, and the temperature was increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 9.89%; at 200°C, the compression deformation percentage of the hot melt film was 99.89%.
[0179] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 55.0% of the total peak area in the XRD spectrum.
[0180] Under nitrogen atmosphere, when the heating rate is 5° C. / min, the hot melt film is subjected to a TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400° C. is 0.00%, and the weight loss rate at 600° C. is 99.62%.
[0181] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.04%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 15.31%.
[0182] Example 5
[0183] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 132.8°C;
[0184] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.69mm 2 ;
[0185] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.49mm 2 ;
[0186] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction, and the temperature was increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 2.71%; at 200°C, the compression deformation percentage of the hot melt film was 99.14%.
[0187] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 68.2% of the total peak area in the XRD spectrum.
[0188] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.81%.
[0189] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.01%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.71%.
[0190] Example 6
[0191] According to the method of Example 1, the three-layer film structure of the hot melt film is changed to a single-layer structure, the thickness of the hot melt film remains unchanged, and the melting point is 124.5°C;
[0192] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.71mm 2 ;
[0193] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.52mm 2 ;
[0194] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction, and the temperature was increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 2.96%; at 200°C, the compression deformation percentage of the hot melt film was 99.79%.
[0195] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 46.9% of the total peak area in the XRD spectrum.
[0196] Under nitrogen atmosphere, when the heating rate is 5° C. / min, the hot melt film is subjected to a TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400° C. is 0.00%, and the weight loss rate at 600° C. is 99.82%.
[0197] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.02%. At 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.91%.
[0198] Example 7
[0199] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C; the melting point of the support layer is 124.5°C;
[0200] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.86mm 2 ;
[0201] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.67mm 2 ;
[0202] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 12.30%; at 200°C, the compression deformation percentage of the hot melt film was 99.91%.
[0203] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 22.6% of the total peak area in the XRD spectrum.
[0204] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.81%.
[0205] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.03%. At 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 15.11%.
[0206] Example 8
[0207] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C;
[0208] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.68mm 2 ;
[0209] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.47mm 2 ;
[0210] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction, and the temperature was increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 0.51%; at 200°C, the compression deformation percentage of the hot melt film was 97.02%.
[0211] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 58.5% of the total peak area in the XRD spectrum.
[0212] Under nitrogen atmosphere, when the heating rate is 5° C. / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400° C. is 0.00%, and the weight loss rate at 600° C. is 99.88%.
[0213] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.01%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.76%.
[0214] Example 9
[0215] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C;
[0216] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.62mm 2 ;
[0217] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.44mm 2 ;
[0218] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 0.20%; at 200°C, the compression deformation percentage of the hot melt film was 95.93%.
[0219] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 59.1% of the total peak area in the XRD spectrum.
[0220] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.87%.
[0221] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.02%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.35%.
[0222] Example 10
[0223] According to the method of Example 1, the diameter of the first metal material layer is changed to 2.7 mm;
[0224] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.04mm 2 ;
[0225] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.017mm2 .
[0226] Embodiment 11
[0227] According to the method of Example 1, the diameter of the first metal material layer is changed to 2.2 mm;
[0228] The overflow film area of the hot melt film on the surface of the first metal material layer is 3.01mm 2 ;
[0229] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.95mm 2 .
[0230] Example 12
[0231] According to the method of Example 1, the inner diameter of the second metal material layer is changed to 1.0 mm;
[0232] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.07mm 2 ;
[0233] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.03mm 2 .
[0234] Embodiment 13
[0235] According to the method of Example 1, the inner diameter of the second metal material layer is changed to 1.8 mm;
[0236] The overflow film area of the hot melt film on the surface of the first metal material layer is 2.15mm 2 ;
[0237] The inner overflow area of the hot melt film on the surface of the second metal material layer is 2.54mm 2 .
[0238] Embodiment 14
[0239] According to the method of Example 1, the dyne values of the first metal material layer and the second metal material layer are changed to 20.
[0240] Embodiment 15
[0241] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 164.5°C.
[0242] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.49mm 2 ;
[0243] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.43mm 2 ;
[0244] The hot melt film was subjected to a thermal compression test. A force of 0.1N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 0.10%; at 200°C, the compression deformation percentage of the hot melt film was 99.01%.
[0245] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 54.3% of the total peak area in the XRD spectrum.
[0246] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.77%.
[0247] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.01%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 12.01%.
[0248] Example 16
[0249] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C.
[0250] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.82mm 2 ;
[0251] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.66mm 2 ;
[0252] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 6.15%; at 200°C, the compression deformation percentage of the hot melt film was 99.19%.
[0253] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 14.3% of the total peak area in the XRD spectrum.
[0254] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.78%.
[0255] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.02%. At 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.83%.
[0256] Embodiment 17
[0257] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C.
[0258] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.82mm 2 ;
[0259] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.66mm 2 ;
[0260] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 6.15%; at 200°C, the compression deformation percentage of the hot melt film was 99.19%.
[0261] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 59.3% of the total peak area in the XRD spectrum.
[0262] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 89.28%.
[0263] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.02%. At 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.83%.
[0264] Embodiment 18
[0265] According to the method of Example 1, the diameter of the first metal material layer is changed to 2.6 mm, and the inner diameter of the second metal material layer is changed to 1.0 mm;
[0266] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.01mm 2 ;
[0267] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0mm 2 .
[0268] Comparative Example 1
[0269] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C.
[0270] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.91mm 2 ;
[0271] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.65mm 2 ;
[0272] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 15.32%; at 200°C, the compression deformation percentage of the hot melt film was 99%.
[0273] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 57.2% of the total peak area in the XRD spectrum.
[0274] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.79%.
[0275] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.12%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 22.05%.
[0276] Comparative Example 2
[0277] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C.
[0278] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.62mm 2 ;
[0279] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.44mm 2 ;
[0280] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction and the temperature was increased at a rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 0.20%; at 200°C, the compression deformation percentage of the hot melt film was 90.00%.
[0281] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 58.4% of the total peak area in the XRD spectrum.
[0282] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.87%.
[0283] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.01%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 14.73%.
[0284] Comparative Example 3
[0285] According to the method of Example 1, the melting points of the first film layer and the second film layer are changed to 103.2°C.
[0286] The overflow film area of the hot melt film on the surface of the first metal material layer is 0.68mm 2 ;
[0287] The inner overflow area of the hot melt film on the surface of the second metal material layer is 0.47mm 2 ;
[0288] The hot melt film was subjected to a thermal compression test. A force of 0.1 N was applied to the hot melt film in the thickness direction, and the temperature was increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film was 0.51%; at 200°C, the compression deformation percentage of the hot melt film was 79.32%.
[0289] The hot-melt film was subjected to XRD detection, wherein the characteristic peaks of the material included 14.0°, 16.8°, 18.4°, and 21.4°; the total area of the characteristic peaks accounted for 57.5% of the total peak area in the XRD spectrum.
[0290] Under nitrogen atmosphere, when the heating rate is 5°C / min, the hot melt film is subjected to TG thermogravimetric test. The weight loss rate of the hot melt film at 25-400°C is 0.00%, and the weight loss rate at 600°C is 99.28%.
[0291] A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the pressure relief valve is 0.48%, and at 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 11.56%.
[0292] The performance of the batteries prepared in the examples and comparative examples was tested, and the results are shown in Table 1.
[0293] Table 1
[0294] Hot box test Impact resistance test Sealing performance test Example 1 30 / 30 30 / 30 30 / 30 Example 2 30 / 30 30 / 30 30 / 30 Example 3 30 / 30 30 / 30 30 / 30 Example 4 30 / 30 29 / 30 30 / 30 Example 5 28 / 30 30 / 30 30 / 30 Example 6 29 / 30 30 / 30 30 / 30 Example 7 30 / 30 29 / 30 29 / 30 Example 8 29 / 30 30 / 30 30 / 30 Example 9 25 / 30 29 / 30 30 / 30 Example 10 30 / 30 29 / 30 28 / 30 Embodiment 11 30 / 30 30 / 30 30 / 30 Example 12 30 / 30 30 / 30 30 / 30 Embodiment 13 30 / 30 30 / 30 28 / 30 Embodiment 14 30 / 30 22 / 30 23 / 30 Embodiment 15 21 / 30 28 / 30 29 / 30 Example 16 28 / 30 20 / 30 22 / 30 Embodiment 17 20 / 30 24 / 30 23 / 30 Embodiment 18 26 / 30 21 / 30 20 / 30 Comparative Example 1 27 / 30 17 / 30 16 / 30 Comparative Example 2 12 / 30 23 / 30 24 / 30 Comparative Example 3 16 / 30 26 / 30 25 / 30
[0295] In Table 1, the impact resistance test result "22 / 30" of Example 14 is taken as an example, where 30 is the number of test samples and 22 is the number of qualified samples that passed the test. Other data in Table 1 can be obtained in the same way.
[0296] It can be seen from Example 1, Examples 8 to 9 and Comparative Examples 1 to 3 that in the test results of Example 9, when the compression ratio of the hot melt film at 100°C is 0.20%, the hot box test performance is slightly reduced, but it still has excellent impact resistance and sealing performance. When the compression deformation percentage of the hot melt film at 100°C in Comparative Example 1 is greater than 14%, the sealing and impact resistance of the battery core deteriorate; in Comparative Example 2, the compression deformation percentage of the hot melt film at 200°C is 90%, and the hot box performance deteriorates; similarly, in Comparative Example 3, the compression deformation percentage of the hot melt film at 200°C is only 79.32%, and the pass rate of the hot box test is significantly reduced. Therefore, when the compression deformation percentage of the hot melt film is ≤14% at 100°C; and when the compression deformation percentage of the hot melt film is ≥95% at 200°C, the hot melt film can be opened at a specific temperature while having good sealing performance, and timely pressure relief can be performed to avoid safety accidents such as fire and explosion caused by flatulence in the battery core.
[0297] It can be seen from the data of Example 1 and Example 14 that when the dyne value of the first metal material layer of Example 14 decreases, the sealing performance and impact resistance of the battery cell decrease significantly. Therefore, when the dyne value of the metal material layer is ≥24, the bonding with the hot melt film can be strengthened to improve the sealing performance of the pressure relief valve.
[0298] It can be seen from the data of Example 1 and Example 2 that when the metal material of the pressure relief valve is nickel or copper plated with nickel, the thermal conductivity is good, the battery cell hot box, sealing and impact resistance can all meet the requirements, and the prepared products can achieve full compliance.
[0299] It can be seen from the data of Example 1, Examples 3 to 6 and Example 15 that when the melting points of the first film layer and the second film layer of the hot melt film of Example 15 are higher than 135°C, the melting point of the hot melt film does not meet the requirements, resulting in a significant decrease in the hot box performance of the battery cell.
[0300] From the data of Example 1, Example 7 and Example 16, it can be seen that when the total area of the characteristic peaks in the hot melt film XRD spectrum accounts for less than 20% of the total peak area in the spectrum, the crystallinity of the hot melt film decreases, and the impact resistance and sealing performance of the battery cell are significantly deteriorated. Therefore, when the total area of the XRD characteristic peaks of the hot melt film accounts for 20% to 70% of the total peak area in the spectrum, the electrolyte resistance of the material can be improved, and swelling can be avoided in the electrolyte environment of the battery cell for a long time, thereby causing the pressure relief valve to fail, causing the battery cell to swell and leak, thereby ensuring the impact resistance and sealing performance of the battery cell.
[0301] It can be seen from Example 3 and Example 17 that the hot melt film of Example 17 cannot be completely compressed at 200°C, and cannot be completely decomposed in the thermogravimetric test, and the passing rate of the hot box test is significantly reduced. Therefore, the present invention can improve the fit between the hot melt film and the metal of the steel shell battery by controlling the thermal weight loss rate of the hot melt film under different temperature conditions, which is beneficial to the sealing of the battery and prevents leakage. At the same time, it can also be hot-melted at high temperature to provide a heat dissipation channel and improve the safety performance of the battery.
[0302] It can be seen from Example 1, Examples 10 to 13 and Example 18 that compared with Example 1 and Examples 10 to 13, the internal and external overflow glue of Example 18 is very small, and the impact resistance and sealing test performance of the battery cell are deteriorated. If the overflow film area is too small, the adhesion between the first metal material layer, the hot melt film, and the second metal material layer becomes weak. Therefore, the present invention ensures the sealing performance of the pressure relief valve while also ensuring the safety of the battery by controlling the appropriate area of the external overflow glue and the internal overflow glue.
[0303] Therefore, by controlling the parameters of the pressure relief valve, the embodiments 1 to 18 of the present invention can ensure a 66.7% pass rate for the hot box test, impact resistance test and sealing test for the obtained battery cells, and even a 100% pass rate for all three tests.
[0304] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hot melt film, characterized in that: A force of 0.1N is applied to the hot melt film in the thickness direction, and the temperature is increased at a heating rate of 5°C / min. At 100°C, the compression deformation percentage of the hot melt film is ≤14%; at 200°C, the compression deformation percentage of the hot melt film is ≥95%.
2. The hot melt film according to claim 1, characterized in that: In the XRD spectrum of the hot melt film, there are at least three characteristic peaks at a 2θ angle position between 10° and 20°, including a first diffraction peak at a 2θ angle of 13.5° to 14.5°, a second diffraction peak at a 2θ angle of 16.3° to 17.3°, and a third diffraction peak at a 2θ angle of 17.9° to 18.9°; and / or, there is at least one characteristic peak between 20° and 30°; Preferably, in the XRD spectrum of the hot-melt film, the total area of characteristic peaks accounts for 20% to 70% of the total peak area in the XRD spectrum.
3. The hot melt film according to claim 1, characterized in that: Under nitrogen atmosphere, the temperature was raised from 25°C at a rate of 5°C / min, and a TG thermogravimetric test was performed on the hot melt film. When the temperature reached 400°C, the weight loss rate of the hot melt film was ≤5%, and when the temperature reached 600°C, the weight loss rate of the hot melt film was ≥99%.
4. The hot melt film according to claim 1, characterized in that: The hot melt film includes a polyolefin compound; Preferably, the hot melt film comprises one or more of polypropylene, polyethylene, anhydride-modified polypropylene, ethylene-propylene copolymer, butene-ethylene copolymer and metallocene-modified polypropylene.
5. The hot melt film according to claim 1, characterized in that: The hot melt film is a single-layer structure, and the melting point of the hot melt film of the single-layer structure is 90-130°C.
6. The hot melt film according to claim 1, characterized in that: The hot melt film comprises a first film layer, a support layer and a second film layer which are arranged in sequence; The melting point of the first film layer is 90 to 135°C; The melting point of the support layer is 120-170°C; The melting point of the second film layer is 90-135°C; Preferably, the thickness ratio of the first membrane layer, the support layer and the second membrane layer is (0.5-5):1:(0.5-5), and more preferably (1-3):1:(1-3).
7. A battery cell, characterized in that: include: A shell body, wherein the shell body is provided with a liquid injection hole; A pressure relief valve, the pressure relief valve covers the injection hole, the pressure relief valve comprises a first metal material layer, a second metal material layer and a hot melt film arranged between the first metal material layer and the second metal material layer, the hot melt film comprises the hot melt film according to any one of claims 1 to 7.
8. The battery cell according to claim 7, characterized in that: A force of 0.1N is applied to the pressure relief valve in the thickness direction, and the temperature is gradually increased at a heating rate of 5°C / min. Within 100°C, the compression deformation percentage of the pressure relief valve in the thickness direction is ≤1%, and at 100°C to 200°C, the compression deformation percentage of the pressure relief valve in the thickness direction is 7% to 23%.
9. The battery cell according to claim 7, characterized in that: The hot melt film is connected to the first metal material layer, and the surface of the hot melt film connected to the first metal material layer includes C element and O element, and the mass ratio of C element to O element is between 90:10 and 99.9:0.1; And / or, the hot melt film is connected to the second metal material layer, and a surface of the hot melt film connected to the second metal material layer includes C element and O element, and the mass ratio of C element to O element is between 90:10 and 99.9:0.
1.
10. The battery cell according to claim 7, characterized in that: The overflow film area of the hot melt film on the surface of the first metal material layer is 0.03 to 3.5 mm 2 , preferably 0.2 to 3 mm 2 ; The area of the inner overflow film of the hot melt film on the surface of the second metal material layer is 0.01 to 2.7 mm 2 , preferably 0.3 to 1.3 mm 2 .
11. The battery cell according to claim 7, characterized in that: A first film layer is disposed on the surface of the first metal material layer and in contact with the hot-melt film; the dyne value of the first film layer is ≥24; And / or, a second film layer is provided on the surface of the second metal material layer that contacts the hot-melt film; and the dyne value of the second film layer is ≥24.
12. The battery cell according to claim 7, characterized in that: The first metal material layer and the second metal material layer include nickel, nickel alloy or copper-plated nickel; Preferably, the second metal material layer is connected to the shell of the battery core; The second metal material layer is provided with a first pressure relief hole; The hot melt film is provided with a second pressure relief hole.
13. The battery cell according to claim 8, characterized in that: The shell includes a first side wall, the injection hole is arranged on the first side wall, the pressure relief valve covers the injection hole, one side of the second metal sheet of the pressure relief valve is connected to the first side wall, the side of the second metal sheet facing away from the shell is connected to the hot melt film, and the side of the hot melt film layer facing away from the second metal sheet is connected to the first metal sheet.
14. A lithium ion secondary battery, characterized in that: A battery cell comprising any one of claims 7 to 13.
Citation Information
Cited By
Battery
WO2026194416A1